2016
DOI: 10.3109/15622975.2016.1155748
|View full text |Cite
|
Sign up to set email alerts
|

Platelet haemostatic function in psychiatric disorders: Effects of antidepressants and antipsychotic drugs

Abstract: Objectives Platelets, the smallest anucleated blood cells, play an essential role in the first step of complex haemostatic process. This review presents the haemostatic function of blood platelets related to their activation in psychiatric disorders (schizophrenia, depression), the role of antipsychotic and antidepressant medication, and introduces the mechanisms by which activated platelets may be involved in the pathophysiology of these disorders. Methods Platelets are interesting and easily accessible blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 116 publications
1
34
0
1
Order By: Relevance
“…Activated platelets play an important role in psychiatric disorders, including depression (43,44), and high levels are considered to be a risk factor for an increased incidence of cardiovascular and cerebrovascular diseases (45). The activation of platelets, mediated by a number of inflammatory factors, including cytokines, serotonin, glutamate, dopamine and P-selectin, serves an important role in psychiatric disorders (46). In particular, serotonin has been previously reported to be involved in the activation of plasma platelets and accelerate aggregation (47).…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets play an important role in psychiatric disorders, including depression (43,44), and high levels are considered to be a risk factor for an increased incidence of cardiovascular and cerebrovascular diseases (45). The activation of platelets, mediated by a number of inflammatory factors, including cytokines, serotonin, glutamate, dopamine and P-selectin, serves an important role in psychiatric disorders (46). In particular, serotonin has been previously reported to be involved in the activation of plasma platelets and accelerate aggregation (47).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that patients treated with APs alone had an increased transfusion rate (OR, 2.37; 95% CI, 1.04‐2.41). The underlying mechanisms are unclear, although a potential association linking AP drugs to altered PLT function and abnormal bleeding has been reported . Psychiatric disease may also be a risk factor for several other adverse outcomes in THA and TKA …”
Section: Discussionmentioning
confidence: 99%
“…Risk‐factor associations like the ones discussed in the present study are important to ascertain, but the authors wisely stopped short of suggesting a causative relationship. It difficult to determine whether depression or antidepressant use drove the increased VTE risk or even if another related factor (eg, thrombophilia traits, use of other recreational or illicit drugs, presence of BDNF Val66met polymorphism leading to combined prothrombotic and depressive traits) was the major impetus and caused some women to develop VTE, especially because—as the authors point out—the increased VTE risk was seen across several classes of antidepressants, including selective serotonin reuptake inhibitors, which have been reported to inhibit platelet function . This likely relates to the fact that serotonin is a weak platelet agonist but also potentiates stimulation from ADP or thrombin .…”
Section: Introductionmentioning
confidence: 99%
“…It difficult to determine whether depression or antidepressant use drove the increased VTE risk or even if another related factor (eg, thrombophilia traits, use of other recreational or illicit drugs, presence of BDNF Val66met polymorphism leading to combined prothrombotic and depressive traits) was the major impetus and caused some women to develop VTE, especially because—as the authors point out—the increased VTE risk was seen across several classes of antidepressants, including selective serotonin reuptake inhibitors, which have been reported to inhibit platelet function . This likely relates to the fact that serotonin is a weak platelet agonist but also potentiates stimulation from ADP or thrombin . When the reuptake of serotonin is blocked, it cannot be replaced within the dense granules of the platelet and thus is not available to augment the activation response or to help retain procoagulant proteins (fibrinogen, von Willebrand factor, thrombospondin, fibronectin, and α2‐antiplasmin) on their surface …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation